Penerapan Fraud Pentagon pada Fraud Laporan Keuangan Perusahaan - Levia Citta Insani (tesco publisher, 2023)
This research aims to test and analyze the fraud pentagon theory of financial statement fraud using the Beneish M-score Model in infrastructure, utility, transportation, and logistics companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2021 period. The type of data used is secondary data in the form of each company's annual report. The number of samples used in this research was 31 companies. The results of research using E-views version 12 show that: (1) Personal financial needs have a negative effect on fraudulent financial statements. (2) Ineffective supervision has a positive effect on financial statement fraud. (3) Related party. Transactions have no effect on fraudulent financial statements. (4) CEO tenure does not affect financial statement fraud. (5) CEO duality does not affect financial statement fraud. The conclusions in this research imply that personal financial needs have a negative effect on fraudulent financial statements. This research proves that the greater the managerial share ownership, the lower the level of fraud in the company's financial reports. Ineffective supervision has a positive effect on financial statement fraud, proving that the more effective the supervision within the company, the smaller the opportunity for financial statement fraud to occur. Related party transactions have no effect on fraudulent financial statements, this shows that related party transactions carried out by the company have decreased or increased, showing no influence on fraudulent financial statements. CEO tenure does not affect financial statement fraud, this shows that increasing or decreasing the CEO's tenure does not show an influence on financial statement fraud. CEO duality does not affect financial statement fraud, which shows that if there is a CEO who holds concurrent positions that do not comply with regulations, this does not show an influence on financial report fraud.